2023
DOI: 10.14216/kjco.23003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of C-reactive protein-to-prealbumin ratio in predicting early recurrence in resectable pancreatic cancer

Abstract: Purpose: Resectable pancreatic ductal adenocarcinoma (PDAC) has a high risk of recurrence after curative resection; despite this, the preoperative risk factors for predicting early recurrence remain unclear. This study therefore aimed to identify preoperative inflammation and nutrition factors associated with early recurrence of resectable PDAC.Methods: From March 2021 to November 2021, a total of 20 patients who underwent curative resection for PDAC were enrolled in this study. We evaluated the risk factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…In recent years, FPR and CPR have emerged as promising indicators capable of capturing both systemic inflammation and nutritional status in various diseases. This combined index of the FPR and CPR holds potential as a prognostic biomarker in patients with conditions such as tumors ( Matsunaga et al., 2020 ; Sun et al., 2020 ; Maruyama et al., 2022 ; Kwon et al., 2023 ), infectious diseases ( Yue et al., 2015 ; Bi et al., 2022 ), autoimmune diseases ( Cheng et al., 2021 ), and other ailments ( Zang et al., 2020 ; Yamada et al., 2021 ; Huang et al., 2022 ). To date, no studies have examined whether FPR and CPR can assess the prognosis of patients with SFTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, FPR and CPR have emerged as promising indicators capable of capturing both systemic inflammation and nutritional status in various diseases. This combined index of the FPR and CPR holds potential as a prognostic biomarker in patients with conditions such as tumors ( Matsunaga et al., 2020 ; Sun et al., 2020 ; Maruyama et al., 2022 ; Kwon et al., 2023 ), infectious diseases ( Yue et al., 2015 ; Bi et al., 2022 ), autoimmune diseases ( Cheng et al., 2021 ), and other ailments ( Zang et al., 2020 ; Yamada et al., 2021 ; Huang et al., 2022 ). To date, no studies have examined whether FPR and CPR can assess the prognosis of patients with SFTS.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, during inflammatory processes, cytokines such as IL-6, IL-1, and TNF-α also contribute to the decrease of PA levels ( Yue et al., 2015 ). The prognostic potential of PA has been demonstrated in various conditions including acute kidney injury ( Xie et al., 2011 ), tumors ( Kwon et al., 2023 ), infectious diseases ( Bi et al., 2022 ), and heart failure ( Lourenço et al., 2014 ). Although PA demonstrated a good predictive ability for mortality among patients with SFTS (AUC = 0.791), statistical significance was not achieved in the univariate analysis ( P = 0.098), likely due to the limited sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the CRP to prealbumin ratio (CPAR), which is an inflammatory and nutritional marker, has been investigated as a potential prognostic indicator in various cancers [ 6 , 8 ]. In this issue of the Korean Journal of Clinical Oncology , Kwon et al [ 9 ] demonstrated the utility of CPAR in predicting the prognosis of PDAC. The authors aimed to identify patients who were at high risk of early recurrence in cases of resectable PDAC.…”
mentioning
confidence: 99%